Effects of earthworms on soil properties and rice production in the rainfed paddy fields of Northeast Thailand - Choosai, C.; Jouquet, Pascal; Hanboonsong, Y.; Hartmann, Christian (Elsevier, 2010)
Earthworms play an important role in soil fertility because of their effects on soil properties, and especially the creation of casts that usually have different properties than the surrounding soil. If the influence of earthworms on soil properties and plant growth has been extensively studied in aerobic ecosystems, their effects remain largely unknown in partially flooded environments such as paddy fields. The aim of this study was to describe the potential influence of earthworms on soil properties and rice yield in Northeast Thailand.Westudied the abundance of aboveground casts produced by Drawida beddardi in two paddy rice systems (transplanting: TP and direct seeding: DS) and we measured the soil physicochemical properties of casts and their influence on rice growth and yield. Cast abundance was low (250 casts per ha) and not different in TP and DS. Casts appeared as patches of fertility with more fine particle sizes and organic matter contents, a higher CEC, as well as a much higher concentrations of mineral elements (N, P and K). As a consequence, our results suggest that earthworm activity lead to a significant higher rice yield. These results stress the importance earthworms could have in the regulation of rice productivity in paddy fields. More research is now needed to understand the ecological mechanisms that regulate earthworm abundance and activity in these environments.